Training Teachers to Increase Behavior-Specific Praise: A Meta-Analysis. Issue 4 (2nd October 2019) - Zoder-Martell, Kimberly A.; Floress, Margaret T.; Bernas, Ronan S.; Dufrene, Brad A.; Foulks, Samantha L.
Abstract: The purpose of this study was to synthesize the literature in support of training teachers to use behavior-specific praise, which is a strategy used to reduce students' disruptive and off-task behavior as well as prevent students' problem behaviors from occurring. The results of 28 single-case studies examining the effectiveness of training teachers to increase their use of behavior-specific praise were synthesized in this meta-analysis. Overall results suggest that praise training produced a strong effect (Tau-U = 0.85) at increasing teachers' use of behavior-specific praise. Limitations, implications, and future directions of the findings are discussed.